Pro drupal as an enterprise development platform - Kurtz, Jamie; Besluau, Thomas (Apress Imprint: Apress, 2013)
In Pro Drupal as an Enterprise Development Platform authors Jamie Kurtz and Thomas Besluau explain how developers can save themselves time and money, and build their applications faster with fewer bugs by using the Drupal CMS as a foundation for their projects. The days when custom client applications were built entirely from scratch are over. Today, it makes business sense to use a flexible, highly scalable framework such as Drupal, Joomla or DotNetNuke as a foundation. This book focuses on why Drupal makes a particularly strong choice for the majority of developers. With an unprecedented level of community support, tens of thousands of well-proven plug-ins and modules available for download, and advanced content management rules and configuration engines Drupal is flexible enough to provide a firm base upon which almost all enterprise application developers can build their own custom solutions. As this book will make clear, it is no longer necessary for developers to write complex applications entirely from scratch for each of their clients. Instead,they should begin by using an enterprise-class CMS like Drupal to provide a robust foundation for them so that they can concentrate their time and skills into solving the business-specific problems of each individual client maximizing the value that they add to each assignment.